The acid sphingomyelinase/ceramide system in COVID-19 - Kornhuber, Johannes; Hoertel, Nicolas; Gulbins, Erich (Molecular Psychiatry, 2021)
Acid sphingomyelinase (ASM) cleaves sphingomyelin into the highly lipophilic ceramide, which forms large gel-like rafts/platforms in the plasma membrane. We showed that SARS-CoV-2 uses these platforms for cell entry. Lowering the amount of ceramide or ceramide blockade due to inhibitors of ASM, genetic downregulation of ASM, anti-ceramide antibodies or degradation by neutral ceramidase protected against infection with SARS-CoV-2. The addition of ceramide restored infection with SARS-CoV-2. Many clinically approved medications functionally inhibit ASM and are called FIASMAs (functional inhibitors of acid sphingomyelinase). The FIASMA fluvoxamine showed beneficial effects on COVID-19 in a randomized prospective study and a prospective open-label real-world study. Retrospective and observational studies showed favorable effects of FIASMA antidepressants including fluoxetine, and the FIASMA hydroxyzine on the course of COVID-19. The ASM/ceramide system provides a framework for a better understanding of the infection of cells by SARS-CoV-2 and the clinical, antiviral, and anti-inflammatory effects of functional inhibitors of ASM. This framework also supports the development of new drugs or the repurposing of "old" drugs against COVID-19.
CRIS-Team WoS Importer:2021-10-15